(untitled) (Nexo Revista Científica, 2022)
The present work is carried out with the objective of defining the culture media referred by the literature for the proliferation of the Pleurotus genus of edible mushrooms and assessing their application in the conditions of Cuba. The diversity of this genus includes at least 30 species, among them, P. djamor, P. florida, P. pulmonaryius, P. sajor-cajou, P. citrinopileatus and P. ostreatus, for which it is necessary to investigate the properties of the media used in the cultivation of the genus. Their classifications are exposed, according to the nature of their ingredients, the growth promotion of various microorganisms and their purpose, as well as their use. The constituents and conditioning of culture media for edible mushrooms, the most frequent preparation methods used in the preservation of Pleurotus strains, and possible defects in them, caused by incorrect handling, contaminants, pests and diseases, are disclosed, as well as the consumption and marketing of mushrooms.